Efektivitas Media Pembelajaran Interaktif Berbasis Lectora Inspire untuk Meningkatkan Keterampilan Membaca Bahasa Arab Siswa / The Effectiveness of Lectora Inspire-Based Interactive Learning Media to Improve Students' Arabic Reading Skills - Muhamad, Sahrul; Mokoagow, Alfarizi Farhan; Abidin, Munirul (IAI DDI Polewali Mandar, Indonesia, 2023)
This study aims to determine the effectiveness of interactive learning media based on the Lectora Inspire application to improving Arabic reading skills with the trial class being class VII A MTs Negeri 2 Kotamobagu in the 2022/2023 academic year. This research is a type of experimental research used pre-experimental design one group pretes-posttes. The data analysis technique used was paired sample t-test with the hypothesis H0 = There was no increase from the results of the pretest to the posttest after being given the action, and H1 = there was an increase from the results of the pretest to the posttest after being given the action. The results obtained from the pretest and posttest data show that the posttest score of students with an average of 75.67 is greater than the pretest with an average of 39.00, through the calculation of the effectiveness test it is known that Thitung 9,003 > Ttabel 1,761 with a sig value of 0.00 smaller from 0.05. So it is concluded that H1 is accepted and H0 is rejected, this means that interactive learning media using Lectora Inspire is effective in improving the Arabic reading ability of class VII MTs Negeri 2 Kotamobagu. With these conclusions, this media can be a solution for teachers in improving Arabic language skills.Abstrak: Tujuan penelitian ini untuk mengetahui efektivitas media pembelajaran interaktif berbasis aplikasi Lectora Inspire untuk meningkatkan keterampilan membaca bahasa Arab dengan kelas uji coba adalah kelas VII A MTs Negeri 2 Kotamobagu tahun ajaran 2022/2023. Penelitian ini merupakan jenis penelitian eksperimental pre-experimental design one group pretes-posttes. Teknik analisis data yang digunakan yaitu paired sample t-test dengan hipotesis H0 = Tidak terjadi peningkatan dari hasil pretest ke posttest setelah diberi tindakan, dan H1 = terjadi peningkatan dari hasil pretest ke posttest setelah diberi tindakan. Hasil penelitian diperoleh dari data pretest dan posttest menunjukkan nilai posttest siswa dengan rata-rata 75,67 lebih besar dibandingkan pretest dengan rata-rata 39,00, melalui perhitungan uji efektivitas diketahui bahwa Thitung 9,003 > Ttabel 1,761 dengan nilai sig 0,00 lebih kecil dari 0,05. Sehingga diambil kesimpulan bahwa H1 diterima dan H0 ditolak, ini artinya bahwa media pembelajaran interaktif menggunakan Lectora Inspire efektif untuk meningkatkan kemampuan membaca bahasa Arab siswa kelas VII MTs Negeri 2 Kotamobagu. Dengan adanya simpulan tersebut, maka media ini mampu menjadi solusi bagi para pendidik dalam meningkatkan kemampuan berbahasa Arab siswa.